2015
DOI: 10.1111/ijs.12507
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Intracerebral Haemorrhage Expansion with Clinical, Laboratory, Pharmacologic, and Noncontrast Radiographic Variables

Abstract: Clinical and noncontrast radiographic variables only weakly predict hematoma expansion. Examination of other indicators, such as computed tomographic angiography contrast extravasation (the 'spot sign'), may prove more valuable in acute intracerebral haemorrhage care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…Although many studies have investigated unadjusted and adjusted associations between a wide variety of clinical, blood, genetic, imaging, and pharmacological factors and the occurrence of intracerebral haemorrhage growth, only a few prediction models have been developed and the predictors used have varied considerably 7, 8, 9, 10, 11, 51. Since 2011, there has been growing interest in use of the spot sign on CT angiography for predicting intracerebral haemorrhage growth,10, 30 but the clinical utility of the small increase in discrimination that resource-intensive advanced vascular imaging adds to simple clinical and imaging predictors that are available worldwide is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many studies have investigated unadjusted and adjusted associations between a wide variety of clinical, blood, genetic, imaging, and pharmacological factors and the occurrence of intracerebral haemorrhage growth, only a few prediction models have been developed and the predictors used have varied considerably 7, 8, 9, 10, 11, 51. Since 2011, there has been growing interest in use of the spot sign on CT angiography for predicting intracerebral haemorrhage growth,10, 30 but the clinical utility of the small increase in discrimination that resource-intensive advanced vascular imaging adds to simple clinical and imaging predictors that are available worldwide is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Interest has grown in whether a so-called spot sign due to contrast extravasation on additional angiography at the time of diagnostic imaging is a predictor of intracerebral haemorrhage growth 6 . There are several multivariable prediction models for intracerebral haemorrhage growth,7, 8, 9, 10, 11 but the identified predictors have varied across models, and several have relied on CT angiography, 12 which is not readily available in low-income and middle-income countries. Identifying more accurate predictors of intracerebral haemorrhage growth is recognised to be a research priority 13 …”
Section: Introductionmentioning
confidence: 99%
“…While, numerous groups have examined the value of other NCCT markers in predicting hemorrhage expansion, 3,8,9,9,19,20 the data regarding their impact on clinical outcome, remains meager. 13 We found that of these other NCCT markers, only hemorrhage irregularity is independently associated with worse functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The association between hemorrhage-expansion and global heterogeneity of the hemorrhage, though, was replicated in at least two different settings. 26,3335 …”
Section: Ncct Biomarkers Of the Risk Of Hemorrhage-expansionmentioning
confidence: 99%